ANALISIS PENGARUH VARIABEL MAKRO EKONOMI TERHADAP INVESTASI ASING LANGSUNG (STUDY KASUS CHINA-INDONESIA). - Ririn Martini Rezki; Yeniwati Yeniwati; Mike Triani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2017)
This research to analyze the influence of macro economic variables impact on Chinese Foreign Direct Investment in Indonesia. The influence of China’s economic growth, Indonesia’s economic growth, interest rates, inflation and exchange rates against Foreign Direct Investment (FDI) China in Indonesia in the long term and short term. Type of this research is descriptive research, the secondary data use form time series data, from 2001Q1 – 2016Q4, taken  from agencies and related institution, the analysis using the Ordinary Least Square (OLS) and Error Correction Model (ECM) to see the influence in a long term and impact in the short term. This research show that Indonesia’s economic growth of China’s economic growth and inflation is have a significant effect in the long term Chinas’s FDI in Indonesia. Variable economic growth of Indonesia’s, interest rates, inflation, exchange rate in the short term influence China’s Foreign Direct Investment in Indonesia. How ever in the long term interest rates and exchange rate do not influence significantly, to China’s FDI in Indonesia.